2020
DOI: 10.1186/s12906-020-02900-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gallic acid and Myricetin on ovarian cancer models: a possible alternative antitumoral treatment

Abstract: Background: Ovarian cancer is the leading cause of mortality among malignant gynecological tumors. Surgical resection and chemotherapy with intravenous platinum/taxanes drugs are the treatments of choice, with little effectiveness in later stages and severe toxicological effects. Therefore, this study aimed to evaluate the antineoplastic activity of gallic acid (GA) and myricetin (Myr) administrated peritumorally in Nu/Nu mice xenotransplanted with SKOV-3 cells. Methods: Biological activity of GA and MYR was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 40 publications
1
31
0
1
Order By: Relevance
“…Tumors in experimental animals or in human body are known to affect many functions of the vital organs. Ascites is a prognostic sign of advanced cancer stage and their inflammatory infiltrate cells and cytokines may affect many functions of the vital organs, especially the liver, kidney, and spleen, even when the site of the tumor does not interfere directly with organ function [13,41,42]. EAT cell inoculation into the mice causes changes in the balance of the antioxidant/oxidative stress system both in EAT and liver tissue [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumors in experimental animals or in human body are known to affect many functions of the vital organs. Ascites is a prognostic sign of advanced cancer stage and their inflammatory infiltrate cells and cytokines may affect many functions of the vital organs, especially the liver, kidney, and spleen, even when the site of the tumor does not interfere directly with organ function [13,41,42]. EAT cell inoculation into the mice causes changes in the balance of the antioxidant/oxidative stress system both in EAT and liver tissue [42].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that GA and CA have antioxidant, anti-inflammatory, anti-mutagenic, anti-carcinogenic, anti-neoplastic, and apoptotic activities [3,8,9]. Furthermore, GA and CA have also been shown to suppress cell viability, proliferation, invasion, and angiogenesis in many human and animal cancer cell lines and in animal models [3,[10][11][12][13][14][15]. Thus, Liu et al [16] have shown that GA selectively induces apoptosis in pancreatic cancer cells without affecting the survival of normal cells, whereas Ho and colleagues [17] have shown that GA inhibits gastric cancer cell growth by modulating the levels of MMP-2 and -9 and cytoskeletal reorganization.…”
Section: Introductionmentioning
confidence: 99%
“…These dyes stain the nuclei in blue-purple, and the cytoplasm with different shades of pink (Varela-Rodríguez et al, 2020). Tissue sections were first post-fixed with 10% paraformaldehyde for 5 minutes and rinsed with tap water.…”
Section: Hematoxylin and Eosin Stainingmentioning
confidence: 99%
“…These dyes stain the nuclei in blue-purple, and the cytoplasm with different shades of pink (Varela-Rodríguez et al, 2020). Tissue sections were first post-fixed with 10% paraformaldehyde for 5 min and rinsed with tap water.…”
Section: Hematoxylin and Eosin Stainingmentioning
confidence: 99%